Consensus guidelines for the diagnosis and treatment of multiple sclerosis. (June 2013) - Yamout, B.; Alroughani, R.; Al-Jumah, M.; Khoury, S.; Abouzeid, N.; Dahdaleh, M.; Alsharoqi, I.; Inshasi, J.; Hashem, S.; Zakaria, M.; ElKallab, K.; Alsaadi, T.; et al.
Abstract The diagnosis of multiple sclerosis (MS) is dependent on the presence of clinical and paraclinical evidence demonstrating dissemination of central nervous system lesions in both space and time, as well as the exclusion of other disorders. Diagnostic criteria were originally promulgated in 1965 by the Schumacher committee and modified subsequently by the Poser committee to include paraclinical evidence. The most recent criteria are the 2010 modifications of the 2001 McDonald criteria, which are focused on making an earlier diagnosis of MS. This article provides guidelines, derived from clinical experience as well as evidence-based medicine, for the diagnosis and management of MS with special emphasis on practices in the Middle East.